(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This paper explores the era of Amir Temur (Tamerlane) with a particular focus on the philosophical foundations of military order and discipline during his reign. It examines how Amir Temur’s leadership and strategic vision shaped a unique system of military organization based on strict discipline, ethical principles, and efficient command structures. The study highlights the significance of these principles in maintaining the strength and stability of his empire, contributing to his success as a military commander and statesman. Through historical analysis, the research reveals the integration of philosophical ideas into practical military governance, reflecting the broader cultural and intellectual context of the time.